2016
DOI: 10.1002/tox.22089
|View full text |Cite
|
Sign up to set email alerts
|

Acteoside‐mediates chemoprevention of experimental liver carcinogenesis through STAT‐3 regulated oxidative stress and apoptosis

Abstract: In the absence of an effective therapy against Hepatocellular Carcinoma (HCC), chemoprevention remains an important strategy to circumvent morbidity and mortality. Here, we examined chemopreventive potential of Acteoside (ACT), a plant derived phenylethanoid glycoside against an environmental and dietary carcinogen, diethylnitrosamine (DEN)-induced rat hepatocarcinogenesis. ACT treatment (0.1 and 0.3% supplemented with diet) started 2 weeks before DEN challenge and continued for 18 weeks thereafter, showed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Together, this might have potentially contributed to the genotoxic effect of CoCl 2 . The involvement of oxidative stress, inflammation, and apoptosis and their relationship with genotoxicity has been reported elsewhere . However, prolonged oxidative stress can lead to chronic inflammation which in turn might serve as a link to some chronic diseases such as cancer, diabetes and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 84%
“…Together, this might have potentially contributed to the genotoxic effect of CoCl 2 . The involvement of oxidative stress, inflammation, and apoptosis and their relationship with genotoxicity has been reported elsewhere . However, prolonged oxidative stress can lead to chronic inflammation which in turn might serve as a link to some chronic diseases such as cancer, diabetes and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 84%
“…Water immersion restraint stress (WIRS) is one of the most widely used models to discover gastric mucosal damage in animals (Jaggi et al 2011) Stress response occurs via the hypothalamic–pituitary–adrenal axis and the sympathetic-adrenal system (Ohta et al 2009). Serum levels of CORT, IL-17 and IFN-γ increase after stress treatment (Blossom et al 2016; Guo et al 2009; Peerzada et al 2016). Studies show that stress causes gastrointestinal disorders, such as irritable bowel syndrome (Ohta et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, numerous studies have shown that VB effectively increases cancer cell apoptosis. For instance, VB promotes apoptosis by activating the HIPK2–p53 signaling pathway in colorectal cancer cells, exerts a tumor‐suppressive function by inducing apoptosis in human immortalized myelogenous leukemia and suppresses tumorigenicity through pro‐apoptosis in hepatocellular carcinoma cells . However, the literature on VB's anticancer activity toward different tumor types has not been sufficiently considered .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, VB promotes apoptosis by activating the HIPK2-p53 signaling pathway in colorectal cancer cells, 10 exerts a tumorsuppressive function by inducing apoptosis in human immortalized myelogenous leukemia 15 and suppresses tumorigenicity through pro-apoptosis in hepatocellular carcinoma cells. 5 However, the literature on VB's anticancer activity toward different tumor types has not been sufficiently considered. 10,11,35 Our results further demonstrated that VB inhibited cell growth and promoted cell apoptosis in OSCC in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation